2021
DOI: 10.1021/acscatal.1c04054
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Analysis of Key Factors Affecting the Catalysis of Oxidized Carbon Blacks for Cellulose Hydrolysis

Abstract: Carbon black is treated with each of three different oxidizing agents (nitric acid, air, and ozone) to introduce oxygencontaining functional groups (OFGs) and the resulting oxidized carbon blacks are used as model catalysts for the hydrolysis of cellulose. At the same time, they are thoroughly characterized by many techniques, especially in terms of surface chemistry, including the type/number of OFGs and the site where OFGs are formed in a carbon structure. Then, by correlating the catalytic activities toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…It has been suggested that the composition in acidic OCFGs (–OH, –COOH, lactone, carboxylic anhydrides) affects the metal particle size distribution by serving as coordination sites for metal cations, greatly dispersing metal particles 13 . Furthermore, several OCFGs can serve as Brønsted acid sites (BAS), e.g., for dehydration, cellulose hydrolysis, etc 14 16 ., or base sites. The relative activity of each type of site is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the composition in acidic OCFGs (–OH, –COOH, lactone, carboxylic anhydrides) affects the metal particle size distribution by serving as coordination sites for metal cations, greatly dispersing metal particles 13 . Furthermore, several OCFGs can serve as Brønsted acid sites (BAS), e.g., for dehydration, cellulose hydrolysis, etc 14 16 ., or base sites. The relative activity of each type of site is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Boehm titration 24 , 25 assumes bases of different strength react with a specific type of OCFGs but is challenged when distinct chemical functions possess similar pK a values. Furthermore, it cannot distinguish aprotic acidic groups (lactones, carboxylic anhydrides) that can hydrolyze into –OH or –COOH in water or acid/base solutions and does not account for the porosity and material hydrophilicity/hydrophobicity (in the liquid phase) 16 , 17 , 25 . High-resolution X-ray photoelectron spectroscopy (XPS) is sensitive to the elemental composition and the relative carbon fraction in various oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…Although strong acids have often been employed for the hydrolysis of polysaccharides, weak acids including carboxylic and phenolic groups can efficiently cleave glycosidic bonds. [34][35][36] Hexagonal boron nitride (h-BN), having lower acidity than AC-Air, [37,38] produced a small amount of products (entry 5, oligomer 9.1 %C). This material became partially soluble in water after the reaction due to exfoliation.…”
Section: Resultsmentioning
confidence: 99%
“…The difference indicates that surface weak acids produced by air oxidation are active. Although strong acids have often been employed for the hydrolysis of polysaccharides, weak acids including carboxylic and phenolic groups can efficiently cleave glycosidic bonds [34–36] . Hexagonal boron nitride (h‐BN), having lower acidity than AC‐Air, [37, 38] produced a small amount of products (entry 5, oligomer 9.1 %C).…”
Section: Resultsmentioning
confidence: 99%
“…Controlling the spatial interactions of substrates with the surface functional groups of the scaffold catalysts with precision is crucial. In many traditional catalysts, such as activated carbon, there are many functional groups 32 . Although one could determine their ratio, it is hard to distinguish the role of each.…”
Section: Discussionmentioning
confidence: 99%